Violence risk assessment practices in Spain - Andrés Pueyo, Antonio (2016)
While practitioners are routinely faced with the task of assessing the risk of violence, the use of structured methods is neither mandatory nor widespread among mental health, correctional, and law enforcement professionals in Spain. That said, the dichotomous construct of dangerousness that had once been widely accepted by both practitioners and the judiciary has largely been replaced over the course of the 21st century by the continuous construct of risk (Andrés-Pueyo & Redondo-Illescas, 2007). This shift can mainly be attributed to the recognition that unstructured judgments of dangerousness produce poor levels of both predictive validity as well as inter-rater reliability (for a thorough discussion see Andrés-Pueyo & Arbach-Lucioni, 2014). The aim of the present chapter is to consider the history of this conceptual shift, including a discussion of risk assessment tools developed in Spain as well as the identification of future directions for research and practice in the country.Fil: Arbach, Karin. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Córdoba. Instituto de Investigaciones Psicológicas. - Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones Psicológicas; ArgentinaFil: Andrés Pueyo, Antonio. Universidad de Barcelona; Españ